Flow balancing in extrusion dies for thermoplastic profiles. Part III: Experimental Assessment - Nóbrega, J. M. (2010)
A computer code, previously developed by the authors for the automatic die design, is used to optimise the flow distribution in a profile extrusion die using two alternative strategies: one based on length optimisation and the other on thickness optimisation. The numerical predictions are then compared with experimental data gathered during extrusion experiments. The numerical predictions and the experimental results agree within the experimental uncertainty thus showing the effectiveness of the computer code, the optimisation algorithm and the design strategies implemented. Generally speaking, measured and predicted values of pressure drop and flow rate are in good agreement (within 8% and 6%, respectively). It also is confirmed that optimisation based on thickness control leads to final profiles that are more prone to distortion.